2018
DOI: 10.1021/acscombsci.8b00022
|View full text |Cite
|
Sign up to set email alerts
|

Poly-adenine-Coupled LAMP Barcoding to Detect Apple Scar Skin Viroid

Abstract: Apple Scar Skin Viroid (ASSVd), a nonprotein coding, circular RNA pathogen is relatively difficult to detect by immunoassay. We report here a one-step reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay to improve selectivity for diagnostic use in detecting ASSVd in plants. ASSVd RT-LAMP was accelerated using loop primers and was found to be highly sensitive with a detection limit of 10 copies of cDNA-ASSVd within 30 min. Real-time LAMP and melting curve analysis could differentiate be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Nonthiolated poly-adenine (polyA 10 )-linked ZIKV RT-LAMP probes ((5-A 10 -CTG TCC CGT GCA GTG TTT CA-3) (Cosmogenetech, Korea)) were attached to the surface of gold nanoparticles (AuNP, 13 nm) according to a salt-aging method. 12 Briefly, 8.1 nM citrate-stabilized AuNPs were incubated with 5 μM polyadenylated (polyA 10 ) ZIKV LAMP probe overnight at room temperature. The conjugate was then dispersed in 0.1 M NaCl for 30 h at 4 °C, and centrifuged at 13 000 rpm for 20 min at 4 °C for the removal of the unbound barcodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonthiolated poly-adenine (polyA 10 )-linked ZIKV RT-LAMP probes ((5-A 10 -CTG TCC CGT GCA GTG TTT CA-3) (Cosmogenetech, Korea)) were attached to the surface of gold nanoparticles (AuNP, 13 nm) according to a salt-aging method. 12 Briefly, 8.1 nM citrate-stabilized AuNPs were incubated with 5 μM polyadenylated (polyA 10 ) ZIKV LAMP probe overnight at room temperature. The conjugate was then dispersed in 0.1 M NaCl for 30 h at 4 °C, and centrifuged at 13 000 rpm for 20 min at 4 °C for the removal of the unbound barcodes.…”
Section: Methodsmentioning
confidence: 99%
“…Our group and others have shown that loop-mediated isothermal nucleic acid amplication (LAMP) can be used to diagnose infectious agents, including viruses, viroids, and bacteria from various clinical samples. [12][13][14] In the present study, we opted to use reverse transcription LAMP (RT-LAMP), which employs six primers that bind to specic regions on the DNA strands, to detect the presence of ZIKV. Based on our experience, the LAMP method is highly specic and requires only a single temperature for dsDNA product amplication.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are expensive, and time-consuming, and require specialized equipment and staff. Recently, reverse transcription loop-mediated isothermal amplification (RT-LAMP) has been used to detect ASSVd in apple leaves (Lee et al, 2018). However, despite the method's robustness, simplicity, and relevance to resource-limited conditions, its application is constrained by the difficulty of primer design, relatively high temperatures required for incubation, and susceptibility to false-positive visual reactions (Panno et al, 2020).…”
mentioning
confidence: 99%
“…However, the application of RT-PCR is limited by the method's reliance on specialized laboratory equipment, complex reaction conditions, and time-consuming procedures (Henson and French, 1993). A recent study reported that a 30-min RT-RPA assay was highly sensitive, with a detection limit of 10 4 copies of ASSVd cDNA (Lee et al, 2018). RT-LAMP assays require at least four sets of primers and a relatively high reaction temperature.…”
mentioning
confidence: 99%
“…Recently, a novel method has been utilized to detect ASSVd, known as reverse transcription loop-mediated isothermal amplification (RT-LAMP) ( Lee et al, 2018 ). This assay amplifies target DNA or RNA with high sensitivity, efficiency and rapidity under the temperature constantly maintained at 62–65°C.…”
mentioning
confidence: 99%